Industrial planning (U.N. New YorkUS, 1969)
Discusses general criteria to be used in the formulation of industrial plans and examines requirements for implementing them. Considers criteria for evaluating industrial projects to determine whether they are consistent with Government's policy and the over-all industrial programme and whether economically feasible. Discusses requirements for successful implementation of industrial projects. Analyses principal factors influencing location of industry and techniques of regional planning. Examines data required for industrial planning and discusses role of U.N. in assisting developing countries to formulate and implement better plans.
IDS